Effects of soccer ball inflation pressure and velocity on peak linear and rotational accelerations of ball-to-head impacts - Cecchi, N. J.; Monroe, D. C.; Moscoso, W. X.; Hicks, J. W.; Reinkensmeyer, D. J. (Sports Engineering, 2020)
Exposure to head impacts is common in soccer and, in some cases, has been associated with neurocognitive and physiological consequences in soccer players. Ball-to-head impacts are particularly frequent, as soccer players regularly use their heads to pass, clear, and shoot the ball during game play and practice. The attenuation of head accelerations resulting from impact is of interest to promoting athlete brain health and numerical models have suggested that reducing soccer ball inflation pressure can lower head accelerations from ball-to-head impacts. The present study sought to test the effect of ball inflation pressure on peak linear acceleration and peak rotational acceleration of the head in a biomechanical reconstruction of ball-to-head impacts using an anthropomorphic testing device head and neck. Adult-sized soccer balls were inflated to five different pressures (34, 48, 55, 62, and 76 kPa), a range that spanned the lower bound on inflation pressure regulated by Fédération Internationale de Football Association and the National Collegiate Athletic Association (60 kPa). Balls were then thrown via a ball launcher at the forehead of the anthropomorphic testing device at three different velocities (17.3, 19.7, and 22.2 m/s). Repeated-measures analyses of variance, with pressure and velocity as repeated measures, revealed an increase in peak linear acceleration (p = 0.001) and peak rotational acceleration (p = 0.002) with higher ball velocities, and a decrease in peak linear acceleration (p < 0.001) and peak rotational acceleration (p < 0.001) with lower ball pressures. Consistent with previous numerical models, the results of this study suggest that reducing soccer ball inflation pressure may reduce head accelerations of ball-to-head impacts.